The Design and Implementation of a Relational to Network Query Translator for a Distributed Database Management System. - Mahoney,Kevin H (1985)
A translation program was implemented for the translation of generic relational queries into the Data Management Language (DML) of the TOTAL data base management system. The objectives of this thesis were to propose and detail a method of supporting a global relational query language for a heterogeneous distributed database management system (DDBMS), design generic query translators for the translation of global relational queries into local hierarchical and network DML, and partially implement translation software for the conversion of relational queries into TOTAL DML. The initial portion of the thesis presents an overall analysis of data partitioning, query decomposition and global query management in the DDBMS. Specific proposals are advocated concerning the specific approach to be taken toward a global query manager and the design of the global schema over current databases. The second portion formalizes the assumptions and constraints present in the global relational model, and presents generic algorithms for the translation of relational queries into hierarchical and network DML. The last portion details the implementation and testing of the relational to TOTAL translator. The approach used was to take information returned from the local data directory of the distributed database in response to a relational query, and compile that information into a generated Pascal program containing the TOTAL DML commands.